Relationship between plasma chemerin levels and disease severity in COPD patients. (28th July 2014) - Boyuk, Banu; Guzel, Eda C.; Atalay, Hande; Guzel, Savas; Mutlu, Levent C.; Kucukyalçin, Volkan
Abstract Background and Aims Chronic inflammation of the lung is a characteristic finding in chronic obstructive pulmonary disease (COPD). The protein chemerin has been identified in inflammatory fluid and in inflamed tissues. This study aimed to determine the association between serum chemerin levels and the severity of COPD. Methods Forty‐three COPD patients and 38 healthy subjects were enrolled in this study. Fasting plasma samples were obtained from the patient and the control group. Serum chemerin levels were measured using a commercial enzyme‐linked immunosorbent assay. C‐reactive protein levels, the erythrocyte sedimentation rate, and fibrinogen analysis were used to assess the inflammation status of the patients. Spirometric measurements with reversibility testing were performed in all the subjects. Results Serum chemerin levels were significantly elevated in the COPD patients (6.44 ± 0.52 vs 5.22 ± 0.59; P < 0.001). A Mann–Whitney U‐test revealed that the serum chemerin levels of stage 2 COPD patients were higher than those of stage 1 and 3 COPD patients (P = 0.651). Cigarette smoking and plasma chemerin relation was also understudied; however, there was no significant relationship between current smokers and ex‐smokers (P > 0.05). Pearson's correlation analysis indicated that serum chemerin levels were positively correlated only with total cholesterol (T. cholesterol) (P < 0.05, r = 0.382). In the linear regression analysis, chemerin levels were associated with age (β = 0.321), triglycerides (β = 0.299) and T. cholesterol (β = 0.555). Conclusion Our study points to a relation between plasma chemerin levels and COPD. Larger patient groups are needed to verify the role of chemerin in the severity of COPD.